Nucleoside and Non-Nucleoside DOT1L Inhibitors: Dawn of MLLrearranged Leukemia - Cao, Meng; Li, Tong; Chen, Yuxiang; Zhai, Xin (Mini Reviews in Medicinal Chemistry, 2021)
Herein, the underlying role of disruptor of telomeric silencing 1-like (DOT1L) as a therapeutic target for mixed-lineage leukemia (MLL)-rearranged is comprehensively clarified. DOT1L can be aberrantly recruited by an MLL fusion partner, thereby causing the over-expression, of several leukemia relevant genes and eventually leading to leukemia. As the unique histone methyltransferase (HMT), DOT1L possesses the function to specifically methylate H3K79, which was identified as a hallmark of active transcription. Accordingly, blockading of DOT1L has been recognized as an effective approach for cancer treatment. Currently, nucleoside DOT1L inhibitors have been developed successfully with the only EPZ5676 entering phase I clinical trial in 2013, which was validated as ‘orphan drug’ toward MLL-rearranged leukemia by FDA. In order to find compounds with better pharmacokinetic properties as DOT1L inhibitors, other types of non-nucleoside skeletons have also been reported successively.
Keywords: MLL-rearranged leukemia